2001
DOI: 10.1046/j.1365-2818.2001.00784.x
|View full text |Cite
|
Sign up to set email alerts
|

Observation of human dentine by focused ion beam and energy‐filtering transmission electron microscopy

Abstract: Molar dentine was sliced into 100 nm ultrathin sections, by means of a focused ion beam, for observation by energy‐filtering transmission electron microscopy (EFTEM). Within the matrix, crystals approximately 10 nm wide and 50–100 nm long were clearly observed. When carbon and calcium were mapped in electron spectroscopic images by EFTEM, carbon failed to localize in crystals. However, it was found in other regions, especially those adjacent to crystals. Because carbon localizations were thought to reflect the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
19
0

Year Published

2002
2002
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(19 citation statements)
references
References 18 publications
0
19
0
Order By: Relevance
“…On the other hand, Di Renzo et al (2001), using 12% NaOCl exposure up to 48 h and Fourier transform infrared spectroscopy (FT-IRS) to visualize treatment-induced chemical modifications of human dentine surfaces did not find any significant alterations in organic moieties, unless the specimen was previously demineralized. This can be explained by the fact that collagen fibrils in dentine are embedded in hydroxyapatite crystals (Butler 1992, Hoshi et al 2001, and consequently, may not only be protected from chemical attacks, but also shielded from infrared light. Thus, even if hypochlorite does alter the superficial organic matrix, this may not be identified using spectroscopic methods.…”
Section: International Endodonticmentioning
confidence: 99%
“…On the other hand, Di Renzo et al (2001), using 12% NaOCl exposure up to 48 h and Fourier transform infrared spectroscopy (FT-IRS) to visualize treatment-induced chemical modifications of human dentine surfaces did not find any significant alterations in organic moieties, unless the specimen was previously demineralized. This can be explained by the fact that collagen fibrils in dentine are embedded in hydroxyapatite crystals (Butler 1992, Hoshi et al 2001, and consequently, may not only be protected from chemical attacks, but also shielded from infrared light. Thus, even if hypochlorite does alter the superficial organic matrix, this may not be identified using spectroscopic methods.…”
Section: International Endodonticmentioning
confidence: 99%
“…have been observed in other non-biological samples (Hutchinson et al, 2003;Wang et al, 2005;Miller et al, 2005) treated by the FIB. FIB preparation of human dentin was first reported in 2001 (Hoshi, et al, 2001) who used energy-filtered TEM analysis of FIB-prepared samples to study the organicinorganic interface of apatite crystals. This work followed earlier work on FIB preparation of human tooth enamel (Hayashi, 1998;Giannuzzi, 1999).…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, they played integral role in the laying down and maintenance of the calcified matrix in dentin. 31 It is expected that the experimental time period also influenced on the adhesion of PU/nHA with dentin as it was reported that the resorption of synthetic HA in 3 months was only 5.4% and it requires many years for complete resorption. 32 The nano-size and even distribution of the nHA were important for the tissue-bonding ability of the composites.…”
Section: Discussionmentioning
confidence: 99%